2012
DOI: 10.17310/ntj.2012.4.12
|View full text |Cite
|
Sign up to set email alerts
|

Through a Glass Darkly: What Can We Learn About a U.S. Multinational Corporation's International Operations From Its Financial Statement Disclosures?

Abstract: We discuss the accounting rules that apply to reporting a U.S. company's international operations. We use examples to illustrate diversity in accounting and offer caveats for policy makers, standard setters, analysts, and researchers regarding their interpretation and use of fi nancial accounting information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Donohoe et al. () describe the failure of some companies to report their tax haven subsidiaries in their Exhibit 21.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Donohoe et al. () describe the failure of some companies to report their tax haven subsidiaries in their Exhibit 21.…”
mentioning
confidence: 99%
“…However, the data used in the two studies above are self-reported on 10-K Exhibit 21. Donohoe et al (2012) describe the failure of some companies to report their tax haven subsidiaries in their Exhibit 21.…”
mentioning
confidence: 99%
“…Researchers are generally left with data that provide only an external, indirect view of fi rms' operations and internal transactions (Gordon and Hines 2002;Jacob 1996). In addition, there are many challenges in identifying international tax planning from fi nancial statements (see Donohoe et al 2012), leaving researchers to use less conventional methods and data sources. For example, Blouin et al (2012) use proprietary data from the Bureau of Economic Analysis (BEA) to examine transfer pricing within fi rms.…”
mentioning
confidence: 99%
“…10 Given all of this information available to investors without the tax return, opponents of tax return disclosure argue that investors would not find any additional, meaningful information in tax returns (Lenter et al 2003;TEI 2006). However, commentators and academics continue to claim that it is nearly impossible to determine firms' taxable income and taxes payable from financial statements (Hanlon 2003;Mills and Plesko 2003;McGill and Outslay 2004;Donohoe et al 2012).…”
Section: Tax Informationmentioning
confidence: 99%